The land of stories - Worlds collide - Colfer, Chris 1990- (Little, Brown and Company, 2017)
Conner, Bree, and their friends from the Land of Stories discover that the fairytale world and the Otherworld are on a collision course that will open a portal connecting the two dimensions in New York, allowing Morina, the witches, the three literary emperors, and the literary army to enter and take over the city, but can Conner stop them and restore order to the fairytale world without the help of his twin sister Alex, who is in Morina's thrall?
Map on fold-out flyleaf
Keywords: Characters in literature; Magic; Brothers and sisters; Twins; New York (N.Y.); Kinderbuch